Mobile Math learning application For children (Fun Math) - Myrat Durdyyev, Myrat Durdyyev (Universiti Teknologi PETRONAS, 2012)
This project is about evolving Android Application that will carry the board of mobile learning inside, throughout implementing math learning or math practicing theories and methods with proper usability. First of all the author of project has carried out research about math learning and practicing strategies and identified some common-used methods that are used in learning simple math for kids. It was decided that the most appropriate method to be integrated into mobile learning is Inductive and Deductive Methods, which will provide fast learning and efficient time react skills. Far ahead, research continued on mobile learning. How learning ideas and strategies could be implemented in mobile application. Afterward with a humble success, the research part was finished, author switched to learning Google AppInventor web application, which aids to develop software application for running on Android based OS platform. Application has been developed and graphical interface was implemented. After downloading apk file into the phone’s memory, software ran successfully. Surveys were conducted to find out satisfaction of user in using developed app and 9/10 people reported satisfactory functionality of the system, 10/10 reported good usability features, 7/10 reported good design of the interface.